Rewriting the rules of the British economy. Issue 2 (13th September 2017) - Kibasi, Tom
Abstract : The British economy suffers from deep structural problems and is not generating rising prosperity for the majority of the population. Underpinned by an understanding of what makes economies successful in the 21st century, a new settlement must now be forged.